Diet and mortality from common cancers in Brazil: an ecological study - Rosely Sichieri; James E. Everhart; Gulnar A. S. Mendonça
A prospective ecological evaluation of mortality from common malignancies with dietary risk factors and alcohol consumption was carried out among 10 state capitals of Brazil. Regression analysis was used to examine the association of dietary intake with mortality rates of the most common cancers among adults age 30 years and older. Age-adjusted cancer mortality rates varied 2.4 to 3.3 fold across the state capitals. A positive relationship was observed between energy intake and colon, lung, and esophageal cancer (p<=0.02 for each). Colon cancer mortality was positively associated with consumption of total fat, eggs, alcohol, mate tea, cereals, and vegetables (p<=0.01). Lung cancer was positively associated with mate and cereal intake (p<0.05). Stomach cancer was associated with consumption of eggs (p=0.04); and negatively associated with consumption of high fiber foods, fruits, and vitamin A and C (p<=0.05). Esophageal cancer was positively associated with fat intake, mate and cereals (p<=0.05) and negatively associated with vitamin A (p=0.02); prostate cancer was negatively associated with vitamin C (p=0.007). Breast cancer was not associated with any of the factors studied. The marked variation in cancer mortality rates in Brazil may be partially related to the high variation in dietary components or other diet associated factors.